Surgical aspects of acute abdominal pain syndrome in children - Konoplitskyi, Viktor; Pohorilyi, Vasyl; Chornyi, Yevhenii (Pain medicine, 2022)
Acute abdominal pain, which is the leading symptom in the clinic of most diseases of the digestive tract, can be a manifes-tation of acute surgical pathology, trauma or an acute infectious disease. All these pathological conditions, in addition to varying degrees of expressiveness of the painful abdominal syndrome, are accompanied by the formation and development of a true or false “acute abdomen”, which is usually accompanied by symptoms of peritoneal irritation. The article discusses the mechanism of for-mation and spread of abdominal pain syndrome, etiopathogenesis of pain syndrome formation in acute surgical pathology in chil-dren. The most characteristic causes of acute abdominal syndrome in children depending on age are presented. A correctly performed differential diagnosis of acute abdominal pain ensures adequate treatment, including emergency surgical intervention on the or-gans of the abdominal cavity.